Management Information System and Performance of Cement Firms in Southeast Nigeria - Gilbert Ogechukwu Nworie; Benita Chikwadom Oguejiofor (Goodwood Publishing, 2023)
Purpose: The study examined how management information system influences the performance of cement-producing firms in Southeast Nigeria. Specifically, the influence of the transaction processing system, decision support system and executive support system on firm performance was assessed. Research methodology: The research design deployed in the study was a descriptive survey while the population of the study compromised 143 staff in the accounting and management information system departments of the selected four (4) cement companies in Southeast Nigeria. Yamane formula for sample size was applied in determining the sample size of 141 out of the population size of 143. The researchers collected primary data using a structured questionnaire administered to the respondents. Pearson Product Moment Correlational analysis was applied to establish the relationship between the variables of the study at a 5% level of significance. Results: Transaction processing system, decision support system and executive support system have a significant and positive effect on the firm performance of cement-producing companies in Southeast Nigeria. Limitations: The results are more fittingly applicable to only cement manufacturing companies. Therefore, they cannot be generalized to other sub-sectors of the Nigerian manufacturing industry. Also, the findings are valid to the extent that the responses to the questionnaire are free from bias. Contribution: The study contributes to knowledge by filling the gap created by the lack of empirical research that uncovers the influence of management information systems on the performance of cement manufacturing firms in the context of Southeast Nigeria.